Designing Inventory Management Of Finished Goods At PT Sinkona Indonesia Lestari - Zachri, Decky P.; Simatupang, Togar M (The Indonesian Journal of Business Administration, 2013)
Finished goods inventory is very important for all companies, especially companies engaged in the pharmaceutical industry, especially for PT SIL as a manufacturer of quinine and its derivatives. Finished goods inventory at PT SIL in the warehouse are beyond the normal range (> 15000 kg). Â Root cause analysis showed the inventory problems at PT SIL were caused by: (i) PT SIL does not have an alternative strategy of pricing in dealing a price war against competitors, (ii) marketing division cannot utilize various types of promotion in marketing the product PT SIL, (iii) supplier from cinchona bark farmers have different product standards of PTPN VIII and importers, (iv) procurement policy of raw material by marketing divisions is improper to maintain sufficient inventory level, and (v) the ability of marketing division to forecast the demand is very low. Alternative solutions obtained by analyzing the situation of the industry internally and externally, by using value chain and five forces framework by Porter to get the TOWS matrix from PT SIL and quinine industry. That will get the strategy to find an alternative solution. Based on some alternative solutions obtained, then the best business solution to resolve high inventory of finished goods are: (i) PT SIL use quality product to fight a price war, (ii) PT SIL can use certain promotional media as a marketing tool, (iii) PT SIL does counseling to the supplier of cinchona bark farmers, (iv) procurement policy of raw material by marketing divisions is proper to maintain sufficient inventory level, and (v) PT SIL can use simple moving average as a method to conduct sales planning considerations.Â Keywords: supply chain management, quinine industry, inventory finished goods, business strategy.Â